A positive feedback regulation of SnRK1 signaling by autophagy in plants - Yang, Chao; Li, Xibao; Yang, Lianming; Chen, Shunquan; Liao, Jun; Li, Kailin; Zhou, Jun; Shen, Wenjin; Zhuang, Xiaohong; Bai, Mingyi; Bassham, Diane C.; Gao, Caiji (Molecular plant, 2023)
SnRK1, an evolutionarily conserved heterotrimeric kinase complex that acts as a key metabolic sensor in maintaining energy homeostasis in plants, is an important upstream activator of autophagy that serves as a cellular degradation mechanism for the healthy growth of plants. However, whether and how the autophagy pathway is involved in regulating SnRK1 activity remains unknown. In this study, we identified a clade of plant-specific and mitochondria-localized FCS-like zinc finger (FLZ) proteins as currently unknown ATG8-interacting partners that actively inhibit SnRK1 signaling by repressing the T-loop phosphorylation of the catalytic α subunits of SnRK1, thereby negatively modulating autophagy and plant tolerance to energy deprivation caused by long-term carbon starvation. Interestingly, these AtFLZs are transcriptionally repressed by low-energy stress, and AtFLZ proteins undergo a selective autophagy-dependent pathway to be delivered to the vacuole for degradation, thereby constituting a positive feedback regulation to relieve their repression of SnRK1 signaling. Bioinformatic analyses show that the ATG8-FLZ-SnRK1 regulatory axis first appears in gymnosperms and seems to be highly conserved during the evolution of seed plants. Consistent with this, depletion of ATG8-interacting ZmFLZ14 confers enhanced tolerance, whereas overexpression of ZmFLZ14 leads to reduced tolerance to energy deprivation in maize. Collectively, our study reveals a previously unknown mechanism by which autophagy contributes to the positive feedback regulation of SnRK1 signaling, thereby enabling plants to better adapt to stressful environments. Whether and how the autophagy pathway is involved in regulating the activity of SnRK1, an evolutionarily conserved heterotrimeric kinase complex that acts as a key metabolic sensor in maintaining energy homeostasis in plants, remains unknown. This study reveals that autophagy positively regulates SnRK1 signaling under energy-limiting conditions by mediating the selective autophagic degradation of SnRK1 repressors, termed ATG8-interacting FCS-like zinc finger (FLZ) proteins.